Teachers’ Perceptions of Authentic Assessment Implementation in Language and Literacy Learning within Multicultural Secondary School Contexts - Fatkhur Roji; Dina Destari; Noura Rizqyannisa Hidayat (Global Education : International Journal of Educational Sciences and Languages, 2024)
This study investigates teachers' perceptions, experiences, and challenges in implementing authentic assessment in multicultural secondary school classrooms. Authentic assessment, focusing on real-world applications and holistic evaluation, is considered valuable for engaging students and fostering critical thinking. However, teachers in multicultural settings face specific challenges, including cultural sensitivity, time constraints, limited assessment literacy, and institutional policies favoring traditional assessments. Through qualitative, phenomenological research with in-depth interviews of language and literacy teachers, the study examines the benefits and barriers of authentic assessment. The findings indicate that while teachers recognize its pedagogical value, they encounter difficulties such as time limitations, insufficient professional development, and a lack of institutional support. Additionally, adapting assessments to be culturally relevant while ensuring fairness and inclusivity proves challenging. This research contributes to understanding the practical obstacles teachers face when applying authentic assessment in diverse classrooms. It also suggests that enhancing assessment literacy, providing targeted professional development, and revising policies to support flexible assessment approaches could help address these issues. The study emphasizes the need for a more culturally responsive approach to assessment, aiming to better equip students for real-world success while addressing the complexities of multicultural education.